Therapeutic Potential of Sodium Channel Blockers as a Targeted Therapy Approach in KCNA1-Associated Episodic Ataxia and a Comprehensive Review of the Literature - Lauxmann, Stephan; Sonnenberg, Lukas; Koch, Nils A.; Bosselmann, Christian; Winter, Natalie; Schwarz, Niklas; Wuttke, Thomas V.; Hedrich, Ulrike B. S.; Liu, Yuanyuan; Lerche, Holger; Benda, Jan; Kegele, Josua (Frontiers in Neurology, 2021)
Among genetic paroxysmal movement disorders, variants in ion channel coding genes constitute a major subgroup. Loss-of-function (LOF) variants in KCNA1, the coding gene for KV1.1 channels, are associated with episodic ataxia type 1 (EA1), characterized by seconds to minutes-lasting attacks including gait incoordination, limb ataxia, truncal instability, dysarthria, nystagmus, tremor, occasionally seizures, but also persistent neuromuscular symptoms like myokymia or neuromyotonia. Standard treatment has not been developed yet and different treatment efforts need to be systematically evaluated. Personalized therapeutic regimens tailored to disease-causing pathophysiological mechanisms may offer the specificity required to overcome limitations in therapy. Toward this aim, we (i) reviewed all available clinical reports on treatment response and functional consequences of KCNA1 variants causing EA1, (ii) examined the potential effects on neuronal excitability of all variants using a predictive scoring system for ion channel variants based on single compartment conductance-based models, (iii) set out to assess a variety of SCBs (Phenytoin, lamotrigine, carbamazepine, and riluzole) regarding their potential to restore the identified underlying pathophysiological mechanisms of KV1.1 channels and (iv) provide a comprehensive review of the literature considering all types of episodic ataxia. Reviewing the treatment efforts of EA1 patients revealed moderate response to acetazolamide and exhibited the strength of sodium channel blockers (SCBs) in the treatment of EA1 patients. Biophysical dysfunction of Kv1.1 channels is typically based on depolarizing shifts of steady-state activation, leading to a loss-of-function of KCNA1 variant channels. Our model predicts a broadening of the action potentials, a lowered rheobase to more hyperpolarized potentials and an increase of the firing rate. Predicted effects of phenytoin, carbamazepine and riluzole could partially restore the altered gating properties of dysfunctional variant channels. These data strengthen the great potential of SCBs by contributing to functional compensation of dysfunctional Kv1.1 channels, propose riluzole as a new drug repurposing candidate and highlight the role of personalized approaches to develop standard care for EA1 patients. These results could have implications for clinical practice in future and highlight the need for the development of individualized and targeted therapies for episodic ataxia and genetic paroxysmal disorders in general.